The Effect of the Russia-Ukraine Crisis on Price Fluctuations and Trade in Energy Sector in Indonesia - Kharis Surya Wicaksana; Rizki Fadhilah Ramadhan; Muhammad 'Azza Sujaka; Adhen Salahudin Al ayubi Prasojo Prasojo (Pusat Pengembangan Sumber Daya Manusia Minyak dan Gas Bumi, 2022)
Energy is an important factor for the sustainable development of a country. The political crisis that occurred between Russia and Ukraine has had a significant impact on trade and commodity price fluctuations, especially in the energy sector. The sanctions imposed on Russia caused global supply cuts from that country which resulted in limited availability of commodities so that prices rose. The increase in global commodity prices also had an impact on the country of Indonesia. This study aims to analyze the impact of the Eastern European crisis on Indonesia, especially trade and commodity price fluctuations in the energy sector. The method used in this research is a literature study so that relevant information is obtained. then the information is analyzed as Strengths, Weakness, Opportunities, and Threats. The results of the study show Indonesia's economy is currently still quite good, the increase in oil energy commodity prices is detrimental while gas, coal, and CPO are profitable for Indonesia. The crisis that has occurred has had a beneficial or detrimental impact on the Indonesian state.